Intervention and evaluation of the life design counseling: A case study - Wang, Danqi; Liu, Xiping (Frontiers in Psychology, 2023)
This article aims to explore the effectiveness of Life Design Counseling (LDC) for a high school student before choosing the subject. To evaluate LDC outcomes, the Career Adapt-Abilities Scale-China Form was used before and after the intervention. Two measures were used to evaluate the process of LDC: the Innovative Moments Coding System (IMCS) and Future Career Autobiography (FCA). The results show that the LDC approach produced a significant change in career adaptability. In addition, the findings demonstrate a significant narrative movement or change with the evaluation of the process. Implications for future research and practice are discussed.